THE ANALYSIS OF INFLUENCE USE PRODUCTION FACTORS ON RAINFED LOWLAND RICE FARMING IN VILLAGE SERINDANG, DISTRICT OF TEBAS SAMBAS REGENCY - Adi Suyatno, Listiasari, Jajat Sudrajat, (Jurnal Social Economic of Agriculture, 2012)
ABSTRACT This study was aimed to determine the effect of the use of production factors rainfed lowland rice farming in Serindang, Tebas, Sambas regency. The method used in this study was a survey method. The location of research was purposively selected in the Serindang, Sambas by considering of farming was the central high produced of rice and it was the main income for the farmers. The primary data was collected by simple random sampling while secondary data was collected from Central Bureau Statistic (BPS) and Village Chief Office. The numbers of respondents were 37 farmers from 730 populations of rainfed rice farmers. The variables examined in this study covered a land area, number of seeds, Urea fertilizer, NPK fertilizer, the amount of herbicides, insecticides, and the non-family workers. The analysis of production factors use in Serindang was Regression Test Cobb-Douglas function. The results of the analysis showed that the factors of production land area were significantly affect production, while the factors of production of seed, urea fertilizer, NPK fertilizer, herbicides, insecticides and non family workers were not significantly affect production. It was influenced by the use of local seed that was not responding toward fertilizing and erroneously rainfall affected uncontrolled irrigation that was influencing the rice growth. Keywords: Factors of production, rice, rainfed lowland